Geochemistry of Late Triassic weak Peraluminous A-Type Karimun Granite, Karimun Regency, Riau Islands Province - Ronaldo Irzon (Geological Agency, 2017)
DOI: 10.17014/ijog.4.1.21-37Karimun is an island with various geological deposits: tin, granite, sand, and others. The tin deposit in Karimun is related to the granitoid tin belt which extends from Myanmar to western Indonesia. Late Triassic Karimun Granite is composed of quartz, K-feldspar, plagioclase, biotite, and/or muscovite with small amounts of accessory minerals. The granitoid unit is different with other felsic intrusive rocks in Malay Peninsular because of its A-type affinity although it is classified as part of the Tin Islands. All eight samples can be classified as altered rocks since the occurrence of secondary chlorite was identifed both macroscopically and microscopically. Petrography was used to describe the minerals that form the samples, whereas XRF and ICP-MS were used to study Karimun Granite from the geochemical point of view. Harker diagrams confirm that the granites show similarity to other granite units in Malaysia except for CaO. Whalen diagrams indicate the granite as A-type as well as the SiO2, REE, and LILE amounts. REE content in the weak peraluminous granitoid ranges from 183 to 3,296 ppm with Eu and Ce show negative anomalies in the REE spider diagram. Negative anomalies of Eu, Ba, Sr, P, and Ti in normalized spider plot also conclude that the studied granitoid indicates A-type.